Evolution of pulmonary hypertension in interstitial lung disease: a journey through past, present, and future - Arslan, Ahmad; Smith, Jorden; Qureshi, Muhammad Raheel; Uysal, Askin; Patel, Kapil K.; Herazo-Maya, Jose D.; Bandyopadhyay, Debabrata (Frontiers in Medicine, 2024)
Interstitial lung diseases (ILD) are a spectrum of disorders often complicated by pulmonary hypertension (PH) in its course. The pathophysiologic mechanism of WHO group 3 PH is different to other forms of PH. The advent of PH is a harbinger for adverse events like mortality and morbidity, implying that the PH component of disease expedites deteriorated clinical outcomes. In fact, WHO group 3 PH due to ILD has the worse prognosis among all groups of PH. Hence, early detection of PH by a comprehensive screening method is paramount. Given considerable overlap in clinical manifestations between ILD and PH, early detection of PH is often elusive. Despite, the treatment of PH due to ILD has been frustrating until recently. Clinical trials utilizing PAH-specific pulmonary vasodilators have been ongoing for years without desired results. Eventually, the INCREASE study (2018) demonstrated beneficial effect of inhaled Treprostinil to treat PH in ILD. In view of this pioneering development, a paradigm shift in clinical approach to this disease phenotype is happening. There is a renewed vigor to develop a well validated screening tool for early detection and management. Currently inhaled Treprostinil is the only FDA approved therapy to treat this phenotype, but emergence of a therapy has opened a plethora of research toward new drug developments. Regardless of all these recent developments, the overall outlook still remains grim in this condition. This review article dwells on the current state of knowledge of pre-capillary PH due to ILD, especially its diagnosis and management, the recent progresses, and future evolutions in this field.